0 to 5 year-old children hearing appraisal by encephalic trunk audition evoked potentials - Bustamante Mejía, César (2000)
OBJECTIVE: To analyze hearing development and maturation from 0 to 5 years of age by evaluating latency times with encephalic trunk audition evoked potentials (AEP). MATERIAL AND METHODS: Forty-four 0 to 5 year-old patients were grouped by age and AEP performed with identical parameters; all patients were sedated to avoid interference. RESULTS: Latency times decreased as age increased, denoting age/latency time (V wave) relation as indicator of hearing development and maturation. CONclusiOn: In our study, there was an indirect relationship between age and latency time acoording to AEP.